Peran Manajemen dalam Perubahan Organisasi - Iin Kurniati; Firmansyah Firmansyah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2021)
In making this article, the author wants to provide knowledge and explain about the role of management and organizational change, in the face of a work environment that is increasingly dynamic and constantly changing, the field of work is getting narrower, the organization is required to adapt If not then be prepared the organization will collapse. because there are no efforts that can be made in it, this is a consequence of living at this time where competition between organizations is always changing. The global economy brings competitors who come from various places. A successful organization is an organization that can change to face competition, by involving efforts in it such as managing the organization well, being able to quickly develop new innovations and ready to face new competition. The result is, we can find out what strategies can increase change in the organization through the role of this management. The research method we use in this article is Library Research, therefore we hope that the results can be useful for readers